Assessment of Simplified Surveillance for Congenital Rubella Syndrome in Sudan, 2014–2017 - Omayma Abdalla; Nada Ahmed; Hanan Abdo El-Hag Mukhtar; Susan Reef; Jose Hagan; Gavin Grant (Vaccines)
Background/Objectives: Congenital rubella syndrome (CRS) is a constellation of serious multi-organ birth defects following rubella virus infection during early pregnancy. Countries in which rubella vaccination has not yet been introduced can have a high burden of this disease. Data on CRS burden and epidemiology are needed to guide the introduction of a rubella vaccine and monitor progress for rubella elimination, but the multi-system nature of CRS manifestations and required specialized testing creates a challenge for conducting CRS surveillance in developing settings such as Sudan. To enhance data quality, we designed and tested a simplified approach for CRS surveillance in Sudan. Methods: Seven CRS surveillance sentinel sites were set up at general pediatric, eye, and cardiology hospitals in Sudan, using standard definitions for reporting and classifying infants with CRS clinical manifestations. Between 2014 and 2017, we evaluated the system using WHO CRS surveillance monitoring indicators, comparing simplified approaches against a comprehensive one. The simplified approaches included (1) an ophthalmic-focused approach; (2) a heart-focused approach; and (3) a cataract-only approach. Results: Surveillance identified 179 infants with suspected CRS via the comprehensive approach, with 25 infants classified as laboratory-confirmed and 6 as clinically compatible. Surveillance sensitivity was highest for the simplified ophthalmic approach, while cataract-based surveillance had the highest proportion of confirmed cases. Conclusions: Simplified CRS surveillance, particularly focusing on detecting cataracts, can significantly contribute to monitoring the impact of rubella vaccine introduction. It could serve as an initial step towards comprehensive CRS surveillance, providing robust evidence to support rubella and CRS elimination efforts.